Derivational Activity and Valency of Nominal Stems Denoting Person in Modern English - Англицкас, В. (Kalbotyra, 1977)
Patterns used to form abstract and concrete nouns from nominal stems denoting person are numerous in Modern English, and most of them include synonymous suffixes. This suffixal redundancy is to a considerable extent eliminated by different combining power of stems which largely depends on their morphological structure and the character of the stem final.